The Portrayal of Elijah Kamski as a God-like Figure and its Impacts in Detroit: Become Human - Ni Made Natasya Andrea Pariana; Dwi Setiawan (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
This thesis examines the portrayal of Elijah Kamski as a God-like figure in the video game Detroit: Become Human and explores the impacts of his godlikeness. Detroit: Become Human is an interactive drama game developed by Quantic Dream and released in 2018. The narrative centers on androids created by Elijah Kamski, who gain self-awareness and begin to develop human-like empathy. By applying Jones’ (1923) concept of the God Complex and the DSM-5’s (2022) criteria for narcissistic personality disorder, this study identifies key actions and behaviors that contribute to Kamski’s depiction as a God-like figure. Additionally, this analysis incorporates Driscoll’s (2016) “White Man’s God Complex” and Khorram-Manesh’s (2024) work on the impacts of narcissistic leadership to demonstrate how these traits underscore social inequality and societal instability caused by the androids’ creation. This thesis argues that Kamski’s God Complex—an extreme manifestation of narcissism—positions him as a God-like character within the game. His portrayal significantly influences the narrative, leading to the dehumanization and abuse of androids.